A Study of Visual Perception in Individuals with Infantile Cerebral Palsy (ICP): Therapeutic Approaches and Strategies - BEKHTI, Karima; NEDIL, Lamia (Journal of Ecohumanism, 2026)
This study aims to diagnose a significant cohort of children with neuromotor disabilities and to ascertain the impact of these disabilities on visual perception. It seeks to address this population's needs, investigate their condition's underlying causes, and propose diagnostic recommendations in speech-language pathology (orthophony) tailored to the various types and classifications of neuromotor disabilities. These classifications are based on the severity, degree, and diverse symptoms of the disability. The ultimate goals are to identify challenges in the cognitive abilities of affected children, provide support and information to their families, and elucidate preventative measures and therapeutic approaches for visual perception to alleviate their difficulties.The significance of this research lies in its potential benefit to speech-language pathologists dedicated to enhancing their services and its contribution as a scholarly addition to the body of scientific knowledge in studies and research concerning neuromotor disabilities.